Congenital long-QT syndrome in type 1 diabetes: a unique association - Erdal Kurnaz; Şenay Savaş Erdeve; Senem Özgür; Melikşah Keskin; Pınar Özbudak; Semra Çetinkaya; Zehra Aycan (The Turkish Journal of Pediatrics)
In contrast to acquired long QT syndrome (LQTS), congenital LQTS is a relatively rare channelopathy with an incidence of 1/2,500. We describe a patient found to have a prolonged QTc in the setting of newly diagnosed Type 1 DM. To the best of our knowledge, this unique association has not been previously reported. Currently, it is shown that glucose ingestion aggravated cardiac repolarization disturbances in LQT2 patients and prolonged the cardiac repolarization phase in healthy controls. Our case presented to the hospital with syncope after increased glucose level. Therefore, it seems that increased glucose level may have prolonged QTc interval and aggravated cardiac repolarization disturbances in the presented case. By this report, we want to emphasize the importance of hyperglycaemia in congenital LQTS.